Characteristics and predictors of death among hospitalized HIV-infected patients in a low HIV prevalence country: Bangladesh. - Lubaba Shahrin; Daniel T Leung; Nashaba Matin; Mohammed Moshtaq Pervez; Tasnim Azim; Pradip Kumar Bardhan; James D Heffelfinger; Mohammod Jobayer Chisti (PLoS ONE, 2014)
Predictors of death in hospitalized HIV-infected patients have not been previously reported in Bangladesh.The primary aim of this study was to determine predictors of death among hospitalized HIV-infected patients at a large urban hospital in Bangladesh.A study was conducted in the HIV in-patient unit (Jagori Ward) of icddr,b's Dhaka Hospital. Characteristics of patients who died during hospitalization were compared to those of patients discharged from the ward. Bivariate analysis was performed to determine associations between potential risk factors and death. Multivariable logistic regression was used to identify factors independently associated with death.Of 293 patients admitted to the Jagori Ward, 57 died during hospitalization. Most hospitalized patients (67%) were male and the median age was 35 (interquartile range: 2-65) years. Overall, 153 (52%) patients were diagnosed with HIV within 6 months of hospitalization. The most common presumptive opportunistic infections (OIs) identified were tuberculosis (32%), oesophageal candidiasis (9%), Pneumocystis jirovecii pneumonia (PJP) (8%), and histoplasmosis (7%). On multivariable analysis, independent predictors of mortality were CD4 count ≤200 cells/mm3 (adjusted odds ratio [aOR]: 16.6, 95% confidence interval [CI]: 3.7-74.4), PJP (aOR: 18.5, 95% CI: 4.68-73.3), oesophageal candidiasis (aOR: 27.5, 95% CI: 5.5-136.9), malignancy (aOR:15.2, 95% CI: 2.3-99.4), and bacteriuria (aOR:7.9, 95% CI: 1.2-50.5). Being on antiretroviral therapy prior to hospitalization (aOR: 0.2, 95% CI: 0.06-0.5) was associated with decreased mortality.This study showed that most patients who died during hospitalization on the Jagori Ward had HIV-related illnesses which could have been averted with earlier diagnosis of HIV and proper management of OIs. It is prudent to develop a national HIV screening programme to facilitate early identification of HIV.